TRANSFORMATION DIGITAL PAYMENT SYSTEMS AND CHANGES IN PUBLIC TRANSACTION BEHAVIOR A QUALITATIVE STUDY OF E-WALLETS AND QRIS IN TEMBILAHAN - Harbaim Septiadi; Siti Hadijah; Muhammad Fauzan (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2025)
The development of financial technology (fintech) has brought significant changes to the financial system, particularly in digital payment systems. Fintech innovations in the form of digital wallets (e-wallets) and the Quick Response Code Indonesian Standard (QRIS) have encouraged people to shift from cash-based transactions to more practical and efficient non-cash transactions. This transformation of the digital payment system not only impacts the technical aspects of transactions but also influences people's transaction behavior. This study aims to analyze how the transformation of the digital payment system through the use of e-wallets and QRIS influences changes in people's transaction behavior in Tembilahan. This study used a qualitative approach with data collection methods through interviews, observation, and documentation of e-wallet and QRIS users in Tembilahan. The results show that the use of e-wallets and QRIS provides convenience, speed, and flexibility in transactions, thus encouraging people to adopt digital payment systems in their daily lives. Changes in people's transaction behavior are reflected in the increasing frequency of digital payment use, changes in payment method preferences, and reduced dependence on cash. However, this study also found that people's digital literacy levels still vary, and some users still have concerns regarding transaction security and personal data protection. In the local context of Tembilahan, the transformation of the digital payment system is gradual and influenced by community habits, technology experience, and digital payment infrastructure support. This study concludes that e-wallets and QRIS play a strategic role in driving the transformation of the digital payment system and shaping changes in people's transaction behavior. The findings of this study are expected to serve as a reference for the government, digital payment service providers, and future researchers in developing an inclusive and sustainable digital payment system.